Analysis Of The Influence Of Employee Discipline On Employee Performance At Mandiangin Koto Selayan District Bukittinggi City Using Grounded Theory - Azwar, Meiriza; Heikal , Jerry (CV. ITTC INDONESIA, 2024)
This study investigates how the application of discipline can improve employee performance in Mandiangin Koto Selayan District, Bukittinggi City. This research is a type of research that uses qualitative techniques with a grounded theory approach. The author conducted direct interviews with 5 employees in five different fields in Mandiangin Koto Selayan District. Then SWOT analysis, observation, and direct interviews with key, main, and supporting informants were also used in this study. This study shows that employee discipline in Mandiangin Koto Selayan District, Bukittinggi City is influenced by several factors, namely motivation, imitating the behavior of other undisciplined employees, lack of a sense of kinship, employee awareness of discipline, leadership supervision, office environment, reword, work development, employee debt, disciplinary rules, sanctions. From this study it was found that the lack of supervision from superiors who received the highest score of 7 (seven) indicated that the discipline of an employee to improve performance was greatly influenced by supervision from superiors so that they became undisciplined and underperformed because there was no supervision from superiors who became the dominant factor determining discipline. employees from the results of this study.